2022
DOI: 10.3390/ma15072650
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Random Cationic Copolymers as Polyplex-Formation Vectors for DNA

Abstract: Research on the improvement and fabrication of polymeric systems as non-viral gene delivery carriers is required for their implementation in gene therapy. Random copolymers have not been extensively utilized for these purposes. In this regard, double hydrophilic poly[(2-(dimethylamino) ethyl methacrylate)-co-(oligo(ethylene glycol) methyl ether methacrylate] [P(DMAEMA-co-OEGMA)] random copolymers were synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization. The copolymers were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Particularly for the polyplex with the plasmid DNA, it reached 440%, which was too large to be attributed solely to swelling of the polyplex. The following scenario, which is supported by results from a previous study [ 30 , 40 ], is suggested: upon loosening of the polyplex structure, the segments of the long DNA chains can be partially dissociated, and thus, are free to participate in complexation with other polyplexes. Thus, large superaggregates of loose polyplexes were formed.…”
Section: Resultssupporting
confidence: 55%
“…Particularly for the polyplex with the plasmid DNA, it reached 440%, which was too large to be attributed solely to swelling of the polyplex. The following scenario, which is supported by results from a previous study [ 30 , 40 ], is suggested: upon loosening of the polyplex structure, the segments of the long DNA chains can be partially dissociated, and thus, are free to participate in complexation with other polyplexes. Thus, large superaggregates of loose polyplexes were formed.…”
Section: Resultssupporting
confidence: 55%
“…FTIR further con rms the successful quaternization of the PFPE-IEX resin, with typical absorption peaks at 3005 cm − 1 , 1474 cm − 1 , and 950 cm − 1 appearing after quaternization, assigned to the C-H bending and stretching of trimethyl group from quaternized ammonium cations (Fig. 1d) 22,23 . The above results demonstrate the successful preparation of PFPE-IEX and subsequent quaternization of the sorbent to produce PFPE-IEX+.…”
Section: Pfpe-iex + Resin Design and Synthesismentioning
confidence: 60%
“…Owing to the shared chemical composition of DMAEMA and TMAEMA, the majority of absorption peaks, such as C–N and CO, are also present in the FT-IR spectra of the TMAEMA monomer. Meanwhile, absorption peaks at around 950 and 1484 cm –1 are observed in TMAEMA spectra which correspond to the peak of quaternary amine, N + (CH 3 ) 3 . ,, In addition, there is a broad peak located from 3200 to 3700 cm –1 which is ascribed to the O–H functional group of the aqueous solution of the TMAEMA monomer. The peak situated around 1636–1638 cm –1 correspond to the superimposed peaks of CC bond stretching of the alkene group and adsorbed water .…”
Section: Resultsmentioning
confidence: 99%